Pertumbuhan Jumlah Lembaga Pendidikan Aanak Usia Dini DKI Jakarta - Alimudin, Alimudin; Bustomi, Ahmad; Nihwan, Nihwan (Ihya Ulum: Early Childhood Education Journal, 2024)
This article aims to describe the educational growth of early childhood education institutions in DKI Jakarta. Data collection for this article was carried out in July 2022 on the refrensi.kemendikbud.go.id page. DKI Jakarta Province as a barometer of educational growth and development. The Gross Participation Figure (APA) in the DKI Jakarta province from 2015 to 2022 has an average participation of 40.63, less than 50% of the average. Educational institutions in the DKI Jakarta province consist of private and state institutions. Of the 5186 existing institutions, they have status as state institutions and 5021 institutions have private status. has a significant comparison, namely (3:97) %. The establishment of PAUD educational institutions began in 1950. The growth in the number of institutions began to develop from 1985 to 1991, amounting to 120 institutions, and the highest peak growth in the number of institutions from 2013 to 2019 was 1885. DKI Jakarta has 6 regencies and cities each. districts and cities have different numbers. The most numerous institutions are in East Jakarta with a total of 1,703 institutions, second in South Jakarta with a total of 1,153 institutions, third in West Jakarta with 984 institutions, fifth in North Jakarta with 984 and fifth in Central Jakarta with a total of 531 institutions. and finally the Thousand Islands have 34 institutions.